Kompetencje społeczne instruktora pływania = The social competence of swimming instructor - Anna Wiśniewska (Kazimierz Wielki University, 2016)
Wiśniewska Anna. Kompetencje społeczne instruktora pływania = The social competence of swimming instructor. Journal of Education, Health and Sport. 2016;6(9):36-43. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.155067 http://www.ojs.ukw.edu.pl/index.php/johs/article/view/3832       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health  and Sport eISSN  2391-8306  7 © The Author (s)  2016; This article is published  with open  access at Licensee  Open Journal  Systems  of Kazimierz  Wielki  University in Bydgoszcz,  Pola nd Open Access. This article is distributed under the terms of  the  Creative  Commons  Attribution  Noncommercial  License  which permits any  noncommercial  use,  distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/)  which permits unrestricted,  non commercial  use,  distribution and reproduction in any  medium,  provided the  work  is properly       cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License ( http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial  use,  distribution  and reproduction in any medium,  provided the  work is properly    cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.   QUALITY IN SPORT 1 (5) 2016, s. 30-38, e-ISSN 2450-3118 Praca wpłynęła do redakcji 12 II 2016, praca została przyjęta do druku 18 IV 2016 DOI: http://dx.doi.org/10.5281/zenodo.50284 PBN: https://pbn.nauka.gov.pl/sedno-webapp/works/723887     Anna Wiśniewska[1] Uniwersytet Mikołaja Kopernika w Toruniu   Kompetencje społeczne instruktora pływania The social competence of swimming instructor       Streszczenie Wprowadzenie. Współczesny sport jest obecny w życiu coraz większej grupy społecznej, a ta aktywność realizowana jest w każdym wieku. Ważne jest, aby instruktor posiadał kompetencje, czyli dyspozycje osobowościowe, które warunkują skuteczność wykonywania określonych czynności. Cel pracy. Celem artykułu jest wskazanie roli kompetencji społecznych w pracy instruktora pływania. Metody i materiały. Praca opiera się na badaniach jakościowych wyjaśniających. Analizie poddane zostały pogląd  i badania odnoszące się do problematyki objętej zakresem tego artykułu. Wyniki. Kompetencje społeczne stanowią grupę umiejętności niezbędnych do nawiązania relacji partnerstwa  w sporcie. Wnioski. Nie ulega wątpliwości, że brak kompetencji społecznych instruktora pływania, jeśli nie uniemożliwia, to przynajmniej istotnie utrudnia osiągnięcie celu zajęć nauki pływania.   Słowa kluczowe: sport, pływanie, rekreacja ruchowa, kompetencje społeczne, wychowanie       Summary Introduction. Sport in our times is becoming part of the lifestyle in the growing number of people in different social groups and this activity is participated in every age. It is important that the instructor had the competence or personality dispositions that determine the effectiveness of the task in hand . Aim of the study. The aim of this article is identify the role of social skills in work as swimming instructor . Methods and materials.   The studies is based on qualitative research inquiries. In the article analyzed views and studies relating to issues within the scope of this article. Results. Social competences are a group of skills necessary to establish a relationship of partnership in the sport. Conclusions. The lack of social competence, if not impossible, then at least significantly hinders the achievement of the activities of learning to swim.   Keywords: sports, swimming, physical recreation, social skills, education [1] Anna Wiśniewska, e-mail: annawisniewska101@gmail.com